2009
DOI: 10.1152/ajpendo.90885.2008
|View full text |Cite
|
Sign up to set email alerts
|

Muscle inflammatory response and insulin resistance: synergistic interaction between macrophages and fatty acids leads to impaired insulin action

Abstract: Obesity is characterized by adipose tissue expansion as well as macrophage infiltration of adipose tissue. This results in an increase in circulating inflammatory cytokines and nonesterified fatty acids, factors that cause skeletal muscle insulin resistance. Whether obesity also results in skeletal muscle inflammation is not known. In this study, we quantified macrophages immunohistochemically in vastus lateralis biopsies from eight obese and eight lean subjects. Our study demonstrates that macrophages infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
199
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(226 citation statements)
references
References 72 publications
15
199
3
2
Order By: Relevance
“…The link between obesity and increased macrophage content in adipose tissue is well established (36,44,47). In accordance with Varma et al (38), our study indicates that obesity is associated with elevated macrophage infiltration (CD68 mRNA expression) in muscle. Furthermore, our data suggest that a high physical fitness level might be linked to decreased macrophage infiltration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The link between obesity and increased macrophage content in adipose tissue is well established (36,44,47). In accordance with Varma et al (38), our study indicates that obesity is associated with elevated macrophage infiltration (CD68 mRNA expression) in muscle. Furthermore, our data suggest that a high physical fitness level might be linked to decreased macrophage infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…MCP1 is not only involved in the recruitment of macrophages (32) but may also induce insulin resistance in myocytes directly (33,34). Infiltration of inflammatory cells, including macrophages, directly into the inflamed muscle tissue or in the adipose tissue surrounding the muscle fibers has been demonstrated previously (35,36,37,38). These cells are thought to maintain the inflammatory state and may also represent a source of cytokines acting in a paracrine and/or endocrine manner (35).…”
Section: Introductionmentioning
confidence: 97%
“…It has indeed been shown that macrophages resident in these tissues (such as Kupffer cells in the liver) could be activated and induce worsening of insulin sensitivity in obese patients. 39,40 It is known that the nature of macrophages is heterogeneous and their phenotype can be modified in various conditions. 26,41,42 It is therefore important to determine not only the total number of macrophages but also their phenotype in AT.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle-infiltrating macrophages in obesity might affect muscle glucose metabolism via secreted factors that impair glucose homeostasis. Although the rise in human muscle inflammatory genes in obesity and type 2 diabetes correlates with insulin resistance [5], evidence for elevated immune cells in human muscle in obesity and type 2 diabetes is scant and controversial [6,7]. Moreover, the phenotypic polarisation of muscle macrophages in obesity and type 2 diabetes is unknown, as is any possible correlation to metabolic status.…”
Section: Introductionmentioning
confidence: 99%